Production Waste at the Tapioca Processing Factories in Central Highlands - Truc, Phan Thi Thanh; Thao Vy, Nguyen Ngoc (VNU Journal of Science: Policy and Management Studies; Vol 35 No 1, 2019)
Abstract: This paper assesses the situation of production waste at the tapioca starch processing factories in Central Highlands. The results of expert interview and 250 employees’ and factories managers’ structured questionnaires show that the production waste was at a high level due to production imbalance, frequent equipment malfunction and unstandardized production procedures. The paper proposes the signing of contracts between the factories and the local farmer to ensure a production balance, technological upgrades, standardization of production procedures, and the development of relevant policies to encourage the workers to make efforts to enhance the production procedures, which helps factories reduce waste in production. Keywords : Waste, tapioca starch, Central Highlands.